Enhancing Chinese Self-Learning Potential through Artificial Intelligence (AI) Technology and Free Applications - ธรรมเสถียร อารีภา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to examine and analyze the potential of Artificial Intelligence (AI) technology and free applications in supporting Chinese self-learning. The research employs a documentary research method by reviewing academic literature, related studies, and analyzing the functions of 12 Chinese language learning applications: HelloChinese, SuperChinese, Duolingo, TalkPal AI, ChatGPT, Bilibili + AI Subtitles, SuperTest, Chinesimple, Du Chinese, Skritter, Todaii: Easy Chinese, and Chinese Writer Characters. The collected data were then comparatively analyzed in terms of language skills development, AI functions, suitable learner levels, as well as the strengths and limitations of each application. The findings indicate that the applications can be categorized into six groups based on their learning potential: integrated language skill applications, conversation-focused applications, reading-focused applications, writing-focused applications, test preparation applications, and supplementary learning tools. Each application plays a different role in supporting the development of listening, speaking, reading, and writing skills for Chinese language learners at various proficiency levels.